The Influence of Regular Physical Activity on Mental Health among University Students - Ns. Hendrik Probo Sasongko; Siti Juwariyah; Umi Solekah (PT. Anagata Sembagi Education, 2025)
Regular physical activity has long been recognized for its physical health benefits, but its role in promoting mental well-being is gaining increasing attention, especially among university students. This study aims to examine the influence of regular physical activity on various aspects of mental health, including levels of stress, anxiety, depression, and overall psychological well-being. Utilizing a quantitative approach, data were collected from 250 university students through structured questionnaires that measured frequency of physical activity and mental health indicators using validated psychological scales. The results reveal a significant negative correlation between regular physical activity and symptoms of depression and anxiety, while a positive correlation was found with overall mental well-being. Students who engaged in at least 150 minutes of moderate to vigorous physical activity per week reported lower stress levels and greater emotional stability. The findings highlight the importance of incorporating physical activity into students’ daily routines as a preventive strategy for mental health challenges. Universities are encouraged to promote accessible fitness programs and provide awareness about the mental health benefits of exercise. This study contributes to the growing body of evidence supporting physical activity as an effective, low-cost intervention to improve mental health outcomes among young adults.